2017
DOI: 10.3174/ajnr.a5342
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Location of Tumor Predicts the Accuracy of Motor Function Localization in Diffuse Lower-Grade Gliomas Involving the Hand Knob Area

Abstract: BACKGROUND AND PURPOSE:The accuracy of preoperative blood oxygen level-dependent fMRI remains controversial. This study assessed the association between the anatomic location of a tumor and the accuracy of fMRI-based motor function mapping in diffuse lower-grade gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
(64 reference statements)
0
20
0
2
Order By: Relevance
“…The etiology behind this rare symptom is almost exclusively reported to be a cortical infarction [ 3 , 9 – 14 ], with hardly any reference to alternative causes [ 15 ]. Intraoperative cortical stimulation, functional MRI and navigated transcranial magnetic stimulation studies clearly identified the region in the precentral gyrus of the posterior frontal lobe which is associated with hand movements, therefore should be saved during neurosurgical interventions, like resections of primary and metastatic brain tumors in the perirolandic area [ 6 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology behind this rare symptom is almost exclusively reported to be a cortical infarction [ 3 , 9 – 14 ], with hardly any reference to alternative causes [ 15 ]. Intraoperative cortical stimulation, functional MRI and navigated transcranial magnetic stimulation studies clearly identified the region in the precentral gyrus of the posterior frontal lobe which is associated with hand movements, therefore should be saved during neurosurgical interventions, like resections of primary and metastatic brain tumors in the perirolandic area [ 6 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…All datasets used throughout this study are available to the public. Transcriptome data and clinical information of 205 patients of the CGGA cohort [12,13] were obtained from the CGGA website (http://www.cgga.org.cn). The clinical phenotype of 564 patients and expression data of normalized combined the TCGA brain lower-grade glioma (LGG) and glioblastoma multiforme (GBM) were obtained from UCSC Xena website [14] (http://xena.ucsc.edu).…”
Section: Publicly Available Sample Collectionmentioning
confidence: 99%
“…The stimulation protocol was the same as that described previously (17). The Ojemann stimulators with 5-mm diameter were employed to identify the eloquent cortices (intensity, 1-6 mA; frequency, 60 Hz; square wave).…”
Section: Intraoperative Stimulation Protocolmentioning
confidence: 99%